Geochronology and tectonic implications of the "Proterozoic" Seluohe Group at the northern margin of the North China craton - Zhang, Y.; Wu, F.; Wilde, Simon; Zhai, M.; Lu, X.; Zhang, H. (Taylor & Francis Inc., 2008)
The Seluohe Group in southern Jilin Province, northeastern China, is traditionally considered to be Mesoproterozoic in age and to represent a Grenville collisional bell at the northern margin of the North China craton, related to the assembly of the Rodinia supercontinent. Investigations indicate that this group is comprised of volcanic and sedimentary rocks that underwent amphibolite- to greenschist-facies metamorphism and intensive deformation. Zircon U-Pb ages indicate that the gneiss and amphibolites were formed in the Archean and under-went amphibolite metamorphism at ~2.5 Ga. However, rhyolite was erupted at 264 ± 10 Ma and andesites formed during the Late Jurassic at 169-162 Ma. These age data indicate that the Seluohe Group is composed by Late Paleozoic and Mesozoic volcanic rocks, with minor Archean metamorphic rocks. They are not a "group" in the stratigraphic sense, but represent a tectonic mlange. Interestingly, no Proterozoic rocks have been identified. Inherited zircons from volcanic rocks (rhyolite, andesite) and granitic gneiss provide no evidence of a Grenvillian collision. Therefore, the new geochronological data do not support the traditional view that Proterozoic tectono-magmatic events affected the northern margin of the North China craton; hence the conclusion that it took part in the formation and evolution of Rodinia during the Proterozoic is questioned. Ar-Ar mineral ages suggest that the Archean metamorphic rocks were later deformed at ~ 160 Ma, establishing a Jurassic deformational event in the area. Copyright © 2008 by V. H. Winston & Son, Inc. All rights reserved.